Galerie Michael Haas, Galerie Haas & Fuchs Berlin 2010. - Publikation anlässlich 'Art 41 Basel' im Art in Basel, 16.06.2010-20.06.2010; Art, Basel (Berlin : Galerie Haas & Fuchs Berlin Galerie Michael Haas Berlin, 2010)
Picabia, Francis ; Klapheck, Konrad ; Le Corbusier ; Klee, Paul ; Matisse, Henri ; Rousseau, Henri ; Picasso, Pablo ; Fautrier, Jean ; Dubuffet, Jean ; Lueg, Konrad ; Fontana, Lucio ; Wirths, René ; Craig-Martin, Michael ; Blake, Peter ; Gertsch, Franz ; Cornell, Joseph ; Warhol, Andy ; Basquiat, Jean-Michel ; Soutter, Louis ; Heckel, Erich ; Katz, Alex ; Kirchner, Ernst Ludwig ; Rouault, Georges ; Baselitz, Georg ; Räderscheidt, Anton ; Chagall, Marc ; Ottersbach, Heribert C.
boek